Essays on secular stagnation: the debate, Taylor Rules and Risk Premia - Matheus, Giuliana Klotz Santopaolo (2022)
This dissertation provides a background on the secular stagnation debate, focusing on two pillars: (i) weakening of traditional monetary tools, measured by how different Taylor Rules evolved since the 90s until 2020 and the differences of performance prior and after the financial crisis; and (ii) asset’s price inflation, measured by how different observed and expected risk premia evolved in the same periods from the first session. There is evidence for the advanced economies studied, especially United States, that both Taylor Rules and Risk Premia did suffer distortions after the crisis and that aspects of the secular stagnation theory seem to tie well with such distortions. There is no evidence of that, however, for the emerging economies studied (Brazil and Mexico).